Paul Willems: le dernier écrivain belge? - Loriau, Henri-François; Pantkowska, Agnieszka (Studia Romanica Posnaniensia, 2001)
Paul Willems, Flemish writer and playwright, who wrote in French, can be considered along with Suzanne Lilar as one of the last Belgian writers in national understanding of this word. This paper is a proposal of analysis of the last prose writing of Willems Le Pays noyé. As this work can be read as an allegory of Belgian history, attention is drawn to the problem of Belgian identity and its formation process. Moreover the final remarks deal with the attitude of Willems to French language, reflected in his different dramatic writings.